Colloidal Stability of Metal Nanoparticles in Engine Oil under Thermal and Mechanical Load. Issue 9 (8th August 2017) - Jendrzej, Sandra; Gökce, Bilal; Barcikowski, Stephan
Abstract: Extended colloidal stability and high dispersion degree of nanolubricants are required to avoid nanoparticle deposition in combustion engines and to reduce friction and wear. The simple and rapid one‐step technique of pulsed laser ablation in liquids is employed to synthesize precursor‐free and highly dispersed gold nanoparticles in lubricants while the colloidal stability is measured by optical spectroscopy and transmission electron microscopy. A remarkable colloidal stability is determined under engine‐like and ambient conditions for nine months in terms of constant primary particle size. In contrast to additive‐free oils, almost no agglomeration is observed, which might be attributed to the attachment of engine oil additives or pyrolyzed/oxidized molecules to the nanoparticles preventing attractive nanoparticle interactions. Abstract : Nanolubricants with prolonged colloidal stability and high dispersion degree are essential to avoid nanoparticle deposition in combustion engines and to diminish friction and wear. Highly dispersed nanolubricants are synthesized in one step by pulsed laser ablation of gold in engine oil and show remarkable stability without agglomeration formation even under harsh engine‐like conditions.